2017
DOI: 10.1155/2017/8363561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Prognostic Factors of Mortality in Patients with Acute Pancreatitis: A Retrospective Study

Abstract: Early and accurate assessment of severity in acute pancreatitis (AP) is of great importance to provide effective disease management and prevent mortality. In this study, we aim to evaluate early indicators that predict the mortality of AP. We retrospectively analyzed 24-hour clinical characteristics and laboratory data in 166 AP patients recruited between January 2014 and November 2015 in Baotou Central Hospital. In total, 18 patients did not survive the disease. Multivariate logistic regression showed that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Nevertheless, a close correlation between mortality and blood glucose, urea, partial pressure of oxygen, white blood cell count, hemoglobin, total bilirubin and cholesterol was shown in patients with AP, and these lab results serve as prognostic markers for predicting mortality. 9,10 Similar to our outcome findings, in a clinical trial, it was shown that aggressive resuscitation initiated within 4 hours of pancreatitis diagnosis hastened clinical improvement by reducing hemoconcentration and persistent SIRS development. 6 The proportion of patients with clinical improvement, as well as rate of improvement within 36 hours, was higher in the aggressive resuscitation group compared to the standard resuscitation group.…”
Section: Variablesupporting
confidence: 86%
“…Nevertheless, a close correlation between mortality and blood glucose, urea, partial pressure of oxygen, white blood cell count, hemoglobin, total bilirubin and cholesterol was shown in patients with AP, and these lab results serve as prognostic markers for predicting mortality. 9,10 Similar to our outcome findings, in a clinical trial, it was shown that aggressive resuscitation initiated within 4 hours of pancreatitis diagnosis hastened clinical improvement by reducing hemoconcentration and persistent SIRS development. 6 The proportion of patients with clinical improvement, as well as rate of improvement within 36 hours, was higher in the aggressive resuscitation group compared to the standard resuscitation group.…”
Section: Variablesupporting
confidence: 86%
“…On admission albumin levels were found to have poor predictive values for mortality and severity. Previous studies were mainly retrospective and had a much smaller sample size 5 , 19 , 20 . They only assessed the predictive value of serum albumin for persistent organ failure and peripancreatic infection, or were limited to severe AP.…”
Section: Discussionmentioning
confidence: 99%
“…Small retrospective cohort studies have shown that hypoalbuminemia is an independent risk factor for severe AP and in-hospital mortality in adults and children 5 , 6 . Serum albumin has been reported to be associated with persistent organ failure and prolonged hospital stay 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[2,5] However, the Ranson criteria can only be determined after 48 hours of inpatient observation, while the APACHE II scoring system uses a point score based upon initial values of 12 routine physiologic measurements and is very complex to use. [6] The BISAP predicts severity, organ failure and death in AP very well and is as good as APACHE II, [7] but it is also reported to have a suboptimal sensitivity for mortality as well as SAP. [8] Regrettably, universally adopted criteria does not exist owing to their more parameters, low sensitivity, and the complex for quick evaluation.…”
Section: Introductionmentioning
confidence: 99%